A novel strategy utilizing local fracture networks to enhance CBHE heat extraction performance: A case study of the Songyuan geothermal field in China. (15th September 2022) - Gao, Xuefeng; Zhang, Yanjun; Cheng, Yuxiang; Huang, Yibin; Deng, Hao; Ma, Yongjie
Abstract: To overcome the restrictions of the limited heat exchange area of the traditional coaxial borehole heat exchanger (CBHE), an enhanced CBHE is proposed. This strategy significantly improves the heat exchange area by constructing local hydraulic fractures for the low-temperature fluid to pass through. Herein, a thermo-hydraulic coupling model based on the Songyuan geothermal field was established to address the heat extraction performance of 15 fracture networks in the enhanced CBHE. The effects of engineering parameters on the thermal benefits are discussed. Results suggest that the proposed strategy improved the accumulated heat energy by more than 6.5 times. Although the lifetime and production temperature of the system declines with the fracture area growth, the net heat energy is improved due to significant reductions in pump energy consumption. A critical feature of this strategy is configuring the hydraulic fractures connecting the well section rather than simply expanding the stimulation volume. The enhanced CBHE is most sensitive to the injection flow, which controls the response process of the thermal benefits to other engineering parameters. Moreover, fracture permeability plays a dual role in regulating the positive and negative correlations of the net heat energy. This work provides substantial insight into CBHE technology upgrading. Highlights: An enhanced CBHE strategy is proposed for the first time. The effects of 15 fracture networks on heat extraction were evaluated. Heat production is 6.5 times higher than traditional CBHE. Early knowledge of the enhanced CBHE operation optimization.